Affordability of course materials: Reactive and proactive measures at The Ohio State University Libraries. Issue 3 (2nd July 2020) - Dotson, Daniel S.; Olivera, Aaron
Abstract: The Ohio State University Libraries has been working on affordability issues related to course materials for some time. This article details some of those efforts, going into detail about moving from reactive methods of dealing with course materials via instructor-initiated reserve requests to more proactive methods of a general education textbook project and curriculum mapping to provide information about ebooks and streaming media as course content.